If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + 24x + 5y = 0 Solving 1 + 24x + 5y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + 24x + -1 + 5y = 0 + -1 Reorder the terms: 1 + -1 + 24x + 5y = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 24x + 5y = 0 + -1 24x + 5y = 0 + -1 Combine like terms: 0 + -1 = -1 24x + 5y = -1 Add '-5y' to each side of the equation. 24x + 5y + -5y = -1 + -5y Combine like terms: 5y + -5y = 0 24x + 0 = -1 + -5y 24x = -1 + -5y Divide each side by '24'. x = -0.04166666667 + -0.2083333333y Simplifying x = -0.04166666667 + -0.2083333333y
| -2=m-20 | | (3y^2-5y+2)-(5y^2-2y-2)=0 | | 12x^2=60x | | 195=15r | | 12-5x=32 | | x^2-5x-44=0 | | 6x+4y+9y+3x=0 | | 12z+144=15(2) | | 12z+144=15*2 | | 15+5x=50 | | 38=19x | | 8(2n+3)=12 | | 4-9(5b-5)9(-7-6n)+35= | | (4x^2-x+5)=0 | | 6x^2=-3x | | 45x^2-49x+12.25=0 | | 20x^2=0 | | (x^2)+x-80=0 | | (x^2)+3x=240 | | 14m-3p+2m+6p=0 | | 7+9(-2n+9)+1= | | 4n-5n+3(n+4)= | | 2v^2+17v+35=0 | | -6(-6a-3)-2+8a= | | -5p+32=2(p-2) | | 4y-4=2-2(y-1) | | -a+7+5(-4+7a)= | | -6x-2(-5x+9)-3x= | | 3.1(2f+1.2)=0.2(f-6) | | 99-12t-(-7t)-4= | | -4(5+n)+n+6= | | 4m^2-20sm+25s^2=0 |